God's fields landscape, religion, and race in Moravian Wachovia - Ferguson, Leland (Gainesville : University Press of Florida, 2011)
Leland Ferguson's work reconstructing this "secret history" through years of archaeological fieldwork was part of a historical preservation program that helped convince the Moravian Church in North America to formally apologize in 2006 for its participation in slavery and clear a way for racial reconciliation.
A beginning -- St. Philips archaeology -- A unity of brethren -- Landscape and piety -- A town built upon a hillside -- Strangers in the land -- "A suitable quarter" -- A disunity of brethren (with Michele Hughes) -- Grave stories -- "To be reconciled" -- Appendix A. St. Philips Church joins Salem Congregation -- Appendix B. Burials in the Salem Strangers' parish God's acre -- Appendix C. Burials in the African American graveyard.
Includes bibliographical references (p. 247-257) and index.
Description based on print version record.
Keywords: Moravian Church -- North Carolina -- Winston-Salem -- History; Moravians -- North Carolina -- Winston-Salem -- History; African Americans -- North Carolina -- Winston-Salem -- History; Salem (Winston-Salem, N.C.) -- Church history; Slavery -- Religious aspects; Salem (Winston-Salem, N.C.) -- Antiquities; Excavations (Archaeology) -- North Carolina -- Winston-Salem.; Slavery -- North Carolina -- History; North Carolina -- Race relations; African Americans -- North Carolina -- Winston-Salem -- History; Excavations (Archaeology) -- North Carolina -- Winston-Salem.; Moravian Church -- North Carolina -- Winston-Salem -- History; Moravians -- North Carolina -- Winston-Salem -- History; North Carolina -- Race relations; Salem (Winston-Salem, N.C.) -- Antiquities; Salem (Winston-Salem, N.C.) -- Church history; Slavery -- North Carolina -- History; Slavery -- Religious aspects -- Moravian Church; Religion; RELIGION / Christianity / Protestant; Electronic books